Network Security Framework, Techniques, and Design for Hybrid Cloud - Achar, Sandesh (Engineering International, 2021)
Network security is a framework that deals with issuing procedures and policies that will be used to establish and maintain security protocols in a particular organization. The functions related to the network security framework are oriented toward insulating the specific organization from external cyber threats and adversaries. On the other hand, a hybrid cloud is a type of cloud whose function is to allow the running and operating of different applications in various and different environments. The primary technique associated with developing hybrid clouds is the conjunctions between private and public clouds that will allow application portability and management for better and more efficient working of the clouds.
Keywords: Cloud; Security Framework; Hybrid Cloud; Network Security